Strengthening the Business Capacity of MSME in Sumberejo Village, Madiun Regency Through Digital Branding and Digital Marketing - Dharmawan, Gallang Dwikyrana; Muhammad, Rahadian Fattah Fadillah; Ramadhani, Noviana Dipi; Hafizha, Muhammad Luthfi; Yunas, Novy Setia (Sahwahita: Community Engagement Journal, 2024)
Small and Medium Enterprises (SMEs) are one of the strategic microeconomic pillars that must receive attention so that they can be empowered to improve the community's economy. Amid the era of Globalization and Digitalization which is increasingly dynamic, it is necessary to align and provide understanding to all groups, especially SMEs, regarding technology, especially in the field of marketing goods or services. In this modern era, a competent understanding of technology is needed that can help sustain everyday life. Therefore, this community empowerment program is designed as a form of providing understanding and explanation to its participants who are MSME actors in Sumberejo Village. This program is implemented by the MMD 1000 Desa Team of Brawijaya University by holding a Digital branding and Digital Marketing workshop which was conducted in 30 MSME groups in Sumberejo Village. The Workshop activity was held in collaboration with Digital Branding and Digital Marketing practitioners who were competent enough to explain how important the use of technology is for small and medium businesses. The workshop also emphasized direct practice carried out by MSME actors in Sumberejo Village, Madiun. Thus, with the implementation of the Business Empowerment program with Digital Branding and Digital Marketing in Village MSMEs, it is hoped that it can help MSME actors in Sumberejo Village to be one step ahead and be able to understand and implement the advantages of digital marketing that have been explained.